Practical management digest, vol.1 - Ovuorie, Jack Mit (Lagos, Nigeria : Ovuorie Management Associates, 1995)
A weekly management bulleting which discusses various topical management problems. The bound copy of volume one contains a total of 89 articles which were published in 52 editions.
oif 13/07/2018
Loans
Keywords: Management